Limited and periodical solutions of one differential equation and its stochastic analog in the Banach space - Gorodny , M. F. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Theorems are proved on the existence and uniqueness of bounded and periodic solutions of a linear difference equation with operator coefficients in Banach space. For the stochastic analogue of the investigated equation, the existence and uniqueness are proved of solutions of a special form, periodic and stationary in the narrow sense.